Spatio Temporal Modeling in Analyzing Temperature Humidity Index Using Google Earth Engine in South Sulawesi: Impact Analysis and Sustainable Mitigation Efforts - Susiyanti, Susiyanti; Nasrul, Nasrul; Maddatuang, Maddatuang; Ruliana, Ruliana; Maru, Rosmini (Jambura Geoscience Review, 2025)
Climate change is one of the biggest challenges and threats to humanity today whose impact has very high dynamics. The high population density, population number, and population activity cause physical changes that affect the microclimate. Microclimate change can reduce people's thermal comfort/temperature humidity index (THI). The impact felt by the community is in the form of discomfort in outdoor activities, health risks such as heat stress, impact on agriculture and natural resource conservation, and animal health on farms to impact emergency response in disaster situations. Moreover, the summer of 2023, a record-breaking summer in 2023, continues the long-term warming trend, indicating the need for a study on the state of THI. This study aims to analyze THI trends and map the distribution of THI in South Sulawesi Province in 2013-2023. The method used in this study is a quantitative-descriptive method through a remote sensing approach using Google Earth Engine (GEE). The Temperature Humidity Index (THI) of South Sulawesi Province in the 2013-2023 time bracket with a cold category with a THI value of 21 °C has an area of 994384.62 hectares, the comfortable category with a THI value of 21°C – 24°C has an area of 1190393.32 hectares, the fairly comfortable category with a THI value of 24 °C – 26°C has an area of 1810662.30 hectares and the uncomfortable category with a THI value of 26°C has an area of 532780.13 hectares.